АЎДАРМА ӨНЕРИ ҲӘМ ОНЫҢ ӘДЕБИЯТЛАРДЫ БАЙЛАНЫСТЫРЫЎДАҒЫ ХЫЗМЕТИ - Сейтниязова, Г.М. (FAN va JAMIYAT, 2023)
The article deals with the skill of translation and its significance, tasks in connection with literature on the example of modern Kapakalpak poets - the translation of I. Yusupov’s works into Uzbek, some of B. Genjemuratov’s poems into English, a comparative definition of literary translations is given and the translators’ skills are determined.